Comparison Study on the Extraction of Gelatin from Nila Fish (Oreochromis nilotichus) Skin Using Acetic Acid and Citric Acid - Suryanti; Indrati, Retno; Irianto, Hari Eko; Marseno, Djagal Wiseso (Pakistan Journal of Nutrition, 2016)
Methods of gelatin extraction from nila fish (Oreochromis nilotichus) skin were studied using acid treatment (acetic acid or citric acid) at various concentrations (0, 0.05, 0.10, 0.15, 0.20 and 0.25 M) and soaking times (0, 1, 2, 3, 4 and 5 h). Gelatin extracted from nila skin treated with 0.10 M acetic acid for 2 h produced the highest yield (25.33%) with a gel strength of 346.16 g bloom and a molecule size distribution of 38-241 kDa. Gelatin extracted from the skin treated with 0.05 M citric acid for 1 h resulted in a yield of 21.09% with a gel strength of 134.52 g bloom and a molecule size distribution of 23-145 kDa. Gelatin extracted by both acids had similar infra-red absorbance spectra, ranging from 1640 to 1239 cm-1. However, gelatin from nila skin treated with 0.10 M acetic acid for 2 h produced gelatin with a more homogenous molecular microstructure than nila skin treated with 0.05 M citric acid for 1 h.